Effect of parasitic infection on dopamine biosynthesis in dopaminergic cells. (15th October 2015) - Martin, H.L.; Alsaady, I.; Howell, G.; Prandovszky, E.; Peers, C.; Robinson, P.; McConkey, G.A.
Graphical abstract: Highlights: Toxoplasma infection of neurosecretory cells increases the production of dopamine. Infection did not change host TH or DDC. Host DDC was observed in the parasitic vacuole in infected brain cells. Import of host DDC may facilitate DA synthesis in the parasitic vacuole. This would prevent toxicity due to cytosolic unpackaged dopamine. Abstract: Infection by the neurotropic agent Toxoplasma gondii alters rodent behavior and can result in neuropsychiatric symptoms in humans. Little is understood regarding the effects of infection on host neural processes but alterations to dopaminergic neurotransmission are implicated. We have previously reported elevated levels of dopamine (DA) in infected dopaminergic cells however the involvement of the host enzymes and fate of the produced DA were not defined. In order to clarify the effects of infection on host DA biosynthetic enzymes and DA packaging we examined enzyme levels and activity and DA accumulation and release in T. gondii -infected neurosecretory cells. Although the levels of the host tyrosine hydroxylase (TH) and DOPA decarboxylase and AADC (DDC) did not change significantly in infected cultures, DDC was found within the parasitophorous vacuole (PV), the vacuolar compartment where the parasites reside, as well as in the host cytosol in infected dopaminergic cells. Strikingly, DDC was found within the intracellular parasite cysts in infected brain tissue. This finding could provide some explanation for observations of DA within tissue cysts in infected brain as a parasite-encoded enzyme with TH activity was also localized within tissue cysts. In contrast, cellular DA packaging appeared unchanged in single-cell microamperometry experiments and only a fraction of the increased DA was accessible to high potassium-induced release. This study provides some understanding of how this parasite produces elevated DA within dopaminergic cells without the toxic ramifications of free cytosolic DA. The mechanism for synthesis and packaging of DA by T. gondii -infected dopaminergic cells may have important implications for the effects of chronic T. gondii infection on humans and animals.